Application of Reading Skills to Children with Special Needs through NaraMedia at SMPN 8 Tamban - Noortyani, Rusma; Mu’in, Fatchul; Cahaya, Noor; Setiawan, Wawan; Wiranda, Nuruddin (Angstrom Centre of Education, 2023)
This study aims to describe the application of accompanying teachers in developing reading skills for children with needs special at SMPN 8 Tamban. This qualitative research study uses guidelines for interviews, observation, and documentation. The subject of the study is two students in Class VII. The data collection techniques are interviews, observation, tests, and documentation. The research results show that the teacher's efforts in developing reading skills with a manner special and guided through NaraMedia. The application of reading skills to children with special needs as a whole by teachers has used simple or short utterances (consisting of one or two words). The teacher's approach to the three children slowly made them know, understand, and understand when reading.